Don't just "sign"... communicate! A student's guide to the deaf experience - Jay, Michelle (Portland, OR : Judea Medea, LLC, 2014)
"This eye-opening book will ignite your senses and eliminate any misconceptions you may have about the deaf community. Delve into this informative and entertaining collection of personal stories culled from the writings of talented Deaf, deaf, hard of hearing, and late-deafened people. Experience the world from their perspectives and learn what questions and comments are best avoided and what common courtesies are most appreciated. By reading this book, you can immerse yourself in the textured world of the deaf community." - back cover
Keywords: Deaf people; Deafness -- Psychological aspects; Deaf -- United States -- Biography; Deaf; Deafness -- Psychological aspects; United States; Biography